Implementation Of Regional Regulation Number 1 Of 2016 Concerning The Protection And Arrangement Of Traditional Markets Shopping Centers And Modern Stores In The Bangli District - Yoga, Ida Bagus Gede Sedana; Subawa, Made; Subawa, I Made Mulyawan (Al-Makki Publisher, 2024)
In relation to trade, the government sees trade as a very important sector and the spearhead of industry. Without trade, the industrial sector would not run well. On the other hand, without industry, trade would also not be profitable enough to pursue. This research concludes as follows: The implementation of Regional Regulation Number 1 of 2016 concerning the Protection and Arrangement of Traditional Markets, Shopping Centers, and Modern Stores in Bangli Regency has not run optimally, this is due to legal factors, namely the Regional Regulation has not regulated concretely, the implementing apparatus, in this case, the Satpol PP has not dared to act decisively and last but not least the culture of the community has not been supportive, where people are still afraid to act if there are people's markets, shopping centers and supermarkets that violate the provisions and the apparatus is still waiting for superior orders, in this case, the Regent. Obstacles in the implementation of Regional Regulation Number 1 of 2016 concerning the Protection and Arrangement of Traditional Markets, Shopping Centers, and Modern Stores in Bangli Regency include: The legal factors themselves such as laws and regulations governing the arrangement of people's markets, shopping centers and supermarkets have not been implemented properly. Law enforcement factors such as the lack of alertness of officers in terms of taking action against traders who do not have a Trade License.